Implementasi Media Pembelajaran Crossword Puzzle Untuk Meningkatkan Keaktifan Peserta Didik Kelas IX.6 di SMP Negeri 57 Palembang - Saraswati, Melly; Alfiandra; Rita Murniati, Sepertia (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
Based on the results of observations in class IX.6 for the 2022/2023 academic year, it was found that students' less activity was indicated by not paying attention to the teacher in learning, a lack of interest in learning which caused teaching and learning activities in the class’s feel quiet. This study aims to increase the active learning of students in class. This type of research is classroom action research with 3 cycles. The subjects were 30 students consist of 16 male students and 14 female students. Learning activities by applying crossword puzzle learning media. The results showed that the application of TGT type cooperative learning with crossword puzzle learning media had been carried out very well. The active learning of students obtained from the results of observations is in the high category with a percentage of 80.34% and has reached the research target. Based on the results of this study, it can be concluded that crossword puzzle learning media has proven effective in increasing student learning activity in class